Evaluating the impact of transmission range on the performance of VANET - Almohammedi, Akram A.; Noordin, Nor Kamariah; Saeed, Sabri (2015)
Vehicular Ad-hoc Network (VANET) is a sub-class of Mobile Ad-hoc Network. The system has been developed to attain Dedicated Short Range Communication among vehicles (V2V) by consolidating existing technologies in which each vehicle is considered as a node. This type of communication is part of an Intelligent Transportation System application. Importantly, there is still no comprehensive evaluation which portrays the mobility impact on the IEEE 802.11p MAC protocol performance, specifically in V2V communications between high mobility nodes. Moreover, the system performance also subjected to various factors including the transmission range and number of flows that change rapidly in scenarios such as on highway. The main goal of this paper is to evaluate the impact of those factors in VANETs environment using AODV as routing protocol. In order to validate the simulation of VANET, traffic and network simulators (SUMO & NS-2) have been used. The performance is evaluated in terms of packet delivery ratio and end to end delay. The simulation results showed that better performance can be achieved in term of higher PDR and lower end to end delay when the transmission range is less than 500 meters. In contrary, when the transmission range is more than 500 meters, PDR started to decrease and end to end delay increased. The performance also degraded as the number of flows increased.